Bridging Impact and Governance: Exploring the Nexus of Social Entrepreneurship and Politics for Global Challenges - Aryal, Diwakar (Academia Research Journal, 2024)
Social entrepreneurship and politics have traditionally operated in separate domains, yet their convergence offers unparalleled potential for addressing global challenges. This study explores the integration of social entrepreneurial strategies with political governance to combat pressing issues such as climate change, digital inclusion, global health crises, and social empowerment. The objective of the research is to analyze opportunities and challenges within this intersection and propose actionable frameworks for leveraging the strengths of both spheres. Employing a qualitative methodology, this study synthesizes secondary data, including policy reports, case studies, and academic literature, to evaluate the effectiveness of collaborative strategies. Findings reveal that social entrepreneurs can significantly influence policy and implementation by innovating sustainable solutions while policymakers amplify these impacts through scaling and systemic integration. The study concludes that fostering collaboration between social entrepreneurship and politics can yield transformative outcomes, creating a model of governance that is ethical, inclusive, and results-oriented.